Factors affecting gestation length in mares – Literature review (Research, Society and Development, 2021)
Gestation length (TG) in horses is a physiological variable of great economic and clinical importance. For the management in breeding farms requires precise knowledge as to the time of parturition. This variable has a wide variation in comparison with other production animals, it has been considered physiological the interval between 320 to 390 days of gestational. Gestation length can be influenced by several maternal factors (maternal age, number of births, maternal nutrition), fetal (sex of the foal) and environmental factors (location, year of birth, month of birth, weather. Thus, this study aims to present a review of the factors that can influence the length of pregnancy, these being the maternal, fetal, paternal and environmental factors. It is concluded that maternal and fetal factors are already well elucidated as to their relationship with the time of pregnancy, however influence of the stallion, environmental and climatic factors still need further studies in equine specie.